Réponses

2014-05-28T13:29:24+02:00
1) (16-25x²)-3(4-5x) (3x +9)
= (16-625) -12 +15x -9x -27
= -609 -12 +15x -9x -27
= 6x -648

2) pour x= 0
(16 -25* 0²) -3 (4 -5*0) (3*0 +9)
= (16-0) -3 (4 -0) (0 +9)
= 16 -12 -27
= -23

pour x= -1/2
(16 -25* (-1/2²))-3 (4-5*(-1/2)) (3*(-1/2)+9)
= ( 16 +6,25) -3 (4 +2,5) ( -1,5 +9)
= 22,25 -12 -7,5 +4,5 -27
= -46,5 +26,75
= -19,75 ( je pense que cest sa mais je suis pas sur)

pour x= -5,75
(16-25*(-5,75²))-3 (4-5*(-5,75)) (3*(-5,75)+9)
= (16- 826,56) -3 (4+28,75) (-17,25 +9)
= -810,56 -12 -86,25 +510 -27
= -935,81 +510
= -425,81 (je suis pas sur aussi) (mais peut etre que c sa)
Meilleure réponse !
2014-05-28T13:47:09+02:00
Bonjour

H = 16 -25x²
H  = (4 -5x)(4 +5x)

G = (4 -5x)(4 -5x) - 3 (3x+9)
G = (4 -5x)( 4 -5x - 9x -27)
G = (4 -5x)(- 14x - 23)

g = 0
soit 4 -5x = 0
-5x = -4
x = 4/5

soit -14x -23 = 0
- 14x = 23
x = -23/14